The irrationality as burning lava or noisily conversation - Ponce, Héctor (2016)
Epistemology and psychoanalysis methodology are discussed, as well as how to ethically evaluate the recent findings of Freud’s private correspondence, where the recovery of some of his patients he claims to have cured is disputed.The aim is a personal evaluation, the sources are bibliographical, and the conclusions are three in number. 1) In epistemology, psychoanalysis is found within human sciences and Freud created a valuable theory of the mind – that one has several conflicted desires – that allows for new routes to retrospection. 2) In methodology, psychoanalysis is enriched if, instead of appealing to the “laws of the unconscious,” it is inspired by hermeneutics. 3) In ethics, Freud was not truthful to present as completed processes several patients who did not therapeutically get better, and the psychoanalytic community has not spoken up accordingly.